MENINGKATAN KESADARAN KESEHATAN WARGA SEKITAR LINGKUNGAN KAMPUS: PROGRAM KERJA KKN SOSIALISASI CEK KESEHATAN GRATIS - Alfaaza, Muhammad Farih; Lindra, Keisha Farellia Putri; Muchtar, Nabila Ramadhani; Rizky, M. Catur; El-Yunusi, M. Yusron Maulana; Vitrianingsih, Yeni; Ustianti, Titik; Yulius, Andre; Juliarto, Tri Susandhi; Darmawan, Didit; Indayati, Lina Wahyu (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2024)
The free health check outreach program which was held on August 19 2024 in the environment around campus aims to increase awareness and knowledge of the health of the surrounding community. The method used is Participatory Action Research (PAR), this program involves students and residents in the environment around Sunan Giri University Surabaya. The results of the outreach show that it has succeeded in increasing health awareness and knowledge among the community. The success of this program is supported by the use of clear and interactive communication techniques, and also indicates the need for adjustments in information delivery methods for various audience groups. These findings suggest the need for the development of more inclusive health intervention models and studies of the long-term impacts of such programs to strengthen positive outcomes on public health.